SUBSTITUTION OF COMMERCIAL FEED WITH MORINGA LEAF MEAL TO IMPROVE THE PERFORMANCE OF MALE RABBIT - N.M.R. Suarni; N.G.A.M. Ermayanti; N.N. Wirasiti (UNHI Press, 2021)
The aims of this study were to find out the effects of moringa leaf meal substitution in commercial feed on the performance of male rabbits (bucks). Twenty four four months old male rabbits with an average live weight of 1200g were used in this study. There were four treatments in this study including 0% (K0) as control and 15% (K1), 30% (K2), 45% (K3) substitution of moringa leaf meal in commercial feed and each treatment consisted of six replicates. The treatments were carried out for two months. The variables measured were including body weight, feed consumption, feed conversion. The results showed that there were significant differences (P <0.05) performance between all treatments (K1, K2, K3) and the control (K0). Substitution of moringa leaf meal up to 45% in commercial feed increase performance of male rabbit. It was concluded that the moringa leaf meal might be substituted in commercial feed up to 45 % to improve the performance of male rabbits (bucks). To get maximum performance of male rabbit rabbits it should be better substituted the commercial feed with moringa leaf meal is 35%.